Delivery of cannabinoids to specific anatomical regions of the brain following oral administration to reach the site of action for glioblastoma multiforme and multiple sclerosis - Brookes, Alice (2023)
Lipid-based formulations are commonly used to improve the oral bioavailability of poorly soluble therapeutics. More recently, these types of formulations have also been explored more to alter delivery to the brain. Certain fatty acids have been reported to increase the permeability of the protective blood-brain barrier (BBB) in a reversible manner following intravascular (i.v.) administration. However, the effect of fatty acids including oleic, linoleic and myristic acids on the BBB has not been explored following oral administration. The work in this thesis explored the delivery of cannabinoids to their site of action within the brain (for example, the frontal lobe for the treatment of glioblastoma multiforme (GBM), or the temporal lobe for treatment of epilepsy) following oral administration in lipid-based formulations. The cannabinoid cannabidiol (CBD) and a fluorinated derivative of CBD, 4’-fluoro-cannabidiol (4’-F-CBD) were studied, with the hypothesis that 4’-F-CBD would exhibit similar pharmacokinetic (PK) properties to CBD but demonstrate higher delivery to the brain due to the addition of fluorine. The work herein began by exploring the anti-cancer properties of the cannabinoids against the aggressive brain cancer, GBM. Both CBD and 4’-F-CBD were shown to inhibit GBM cell growth and overcome two major resistance mechanisms to the standard treatment of GBM with temozolomide (TMZ). The cannabinoids also demonstrated a synergistic response with imidazotetrazine compounds (TMZ and analogue, T25), where high synergy was observed when cells were exposed to a combination of 4’-FCBD with T25. Preliminary studies investigated the mechanism of anti-cancer activity of CBD, indicating that pathways including DNA-methylation are involved for the first time.